MIS-C and Kawasaki disease: Different illnesses or part of the same spectrum? - Angelo Ravelli (Elsevier, 2024)
During COVID-19 pandemic pediatricians have been challenged by the occurrence of the multisystem inflammatory syndrome in children (MIS-C). This condition displays some features similar to those of Kawasaki disease (KD), but was is characterized by clinical signs and symptoms that are infrequent in this illness, such as diarrhea, abdominal pain, neurologic dysfunction and cardiac involvement, especially myocarditis. Many children with MIS-C necessitated ICU admission due to development of multiorgan failure and circulatory shock, usually of myocardial origin. Management is based on the administration of intravenous immunoglobulin, glucocorticoids and, in the most severe forms, anakinra. The clinical similarities between MIS-C and KD have raised an intense debate about whether they represent different illnesses with overlapping clinical features or are part of the same disease spectrum. Most authorities favor the assumption that MIS-C is distinct from KD, based on epidemiological, clinical and immunological differences between the two entities. Others argue that the two disorders may represent a continuum, with some differences in phenotype and severity being related to viral load or strain or magnitude or kinetics of immune response. The present article is aimed to analyze critically the rationale and evidence in favor of the second hypothesis.